The risk and protective factors for the development of compassion fatigue and burnout in psychologists : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Tomkins, Sharon Heather (Massey University, 1999)
The present study examined how both individual and organisational factors combine in different ways to produce risk and protective factors for the development of compassion fatigue and burnout. The reason for undertaking research into secondary traumatic stress disorder in psychologists is because there seems to be an increase in psychologists leaving the field of psychology due to increased stress and burnout. Several variables were examined, including an investigation between risk and protective factors for the development of compassion fatigue and burnout. These included work settings i.e., public institutions and private practices, full time and part time work, life satisfaction, work locus of control, and intention to quit the field, along with several demographic variables, such as gender. The compassion fatigue and burnout variables correlated with many of the protective and risk factors. Public institutions, external work locus of control, poor life satisfaction, and full time work, all predicted a higher risk of developing either compassion fatigue/burnout or both. The results indicated that compassion fatigue and burnout should be considered as a concern for practitioners, mental health organisations and trainers of future psychologists.
Keywords: Burn out; Psychologists; Job stress